EFT analysis of new physics at COHERENT with Dirac neutrinos - Bresó Pla, Víctor; Cruz-Alzaga, Sergio; González-Alonso, Martín; Prakash, Suraj (Journal of high energy physics, 2025)
We study the sensitivity of COHERENT-like experiments to non-standard contributions within the so-called νWEFT framework. The latter is the most general low-energy effective field theory that includes not only the light SM fields but also additional right-handed Dirac neutrinos. Our analysis includes for the first time flavor-general New Physics effects in neutrino production (pion and muon decays) and neutrino detection (through Coherent Elastic Neutrino-Nucleus Scattering). Despite the generality, the results can be written in compact form and are easy to implement in existing or future analyses using effective nuclear charges. We use current COHERENT data to set constraints on the corresponding effective operators, and we estimate the sensitivity of future measurements.
Gesehen am 02.03.2026